ANALYSIS OF OPPORTUNITIES AND BARRIERS FOR IMPLEMENTING SUSTAINABLE DEVELOPMENT PRACTICES IN AGRO-ENTERPRISES - OHIIENKO, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article analyzes opportunities and barriers to implementing sustainable development practices in agro-enterprises. The research aims to analyze, systematize, and improve the theoretical and methodological framework for implementing sustainable development practices in agro-enterprises. The article discusses current trends in implementing sustainable development principles in the agricultural sector, emphasizing their significance for ensuring socio-economic stability. The research presents a comprehensive approach to managing enterprises, including economic, social, and environmental aspects. It is substantiated that realizing sustainable development principles contributes to increasing enterprises' competitiveness, ensuring food security, and conserving natural resources. The analysis of literary sources confirmed the importance of integrating sustainable development into agro-enterprises' strategies. It was found that the sustainable development of enterprises is not only a contemporary requirement but also a strategic necessity for adapting to changing market conditions. The research also identified the main challenges in implementing the sustainable development strategy, including financial constraints, insufficient awareness among managers, and lack of government support. The article emphasizes that the economic aspect of sustainable development ensures financial stability and enhances resource management efficiency.In contrast, the social aspect focuses on creating favorable working conditions and increasing social responsibility. The environmental aspect, in turn, concentrates on reducing the negative impact of enterprises on the environment through the implementation of energy-efficient technologies and circular economy practices. Methodological recommendations for implementing sustainable development practices are proposed, including assessing the impact of enterprise activities, forming strategic goals, and investing in innovative technologies. Implementing corporate social responsibility policies and ensuring equal opportunities for all employees are essential for sustainable development. The research confirms that integrating sustainable development is a crucial element not only for the economic efficiency of enterprises but also for the social well-being of society.
Keywords: sustainable development; sustainable development practices; agro-enterprise; ecological responsibility; social responsibility